Correlation between Vitalism and Genetics According to the Paradigm of Complexity - Teixeira, Marcus Zulian (Homeopathy, 2020)
Background In homeopathic philosophy, vital force is a non-material substrate that is responsible for maintaining the body's sensations and functions and where homeopathic medicines act. In genetics, the body's vital functions are controlled by biochemical information, which is contained in the cell genome and consists of a protein encoding portion (exome) and another that regulates this encoding scheme (epigenome). Both the philosophical vital force and the genome present properties of complex and dynamic self-organisation systems.Aims This study aimed to explore and develop a philosophical-scientific correlation between vitalism and genetics according to the complexity paradigm.Results Vital principle and genome present inseparable composition among distinct existing components that influence one another and form a network of connections that create complex and dynamic self-organisation behaviour. Described in both models, ‘vortex’ indicates the existence of a force coming from within the system that is externalised as an emergent, information-transmitting phenomenon. Supporting this correlation, some experimental studies show that homeopathic medicines act on the genome by modulating gene expression.Conclusions In line with the similarity of existing characteristics and properties, the genome may be considered as hypothetical biological substrate of organic vital force.
Keywords: homeopathy; vitalism; genetics; epigenetics; complex systems